PEMBUATAN GAME 2D VIRTUAL PET “BARCOMON” DENGAN FITUR BARCODE SCANNER - Hendy Sofjan; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Barcomon” is a virtual pet game for smartphone with an Android Operating System. This game was made using C# programming language and Unity as the development program. In this game, player will act as a Coder with a goal to achieve the Code Master title by winning all the battle on The Forum. Coder must take care and train the monsters. Player can get the monsters by scanning any barcode from any daily product. The testing of this game is done by using a blackbox testing method, alpha testing, and beta testing with a survey distributed to 39 respondents. The survey shows that Barcomon is a game with an interesting gameplay, easy to play, and has a unique barcode scanning feature that is rarely found in other games.